Efficiency and technical progress in agricultural productivity in the European Union - Smędzik-Ambroży, Katarzyna; Sapa, Agnieszka (Efektywność i postęp techniczny w kształtowaniu produktywności rolnictwa UE, 2019)
The aim of this study was to estimate changes in total productivity in agriculture of the EU, the EU 15 and the EU 10 countries and to determine to what extent these changes resulted from technical progress and to what extent from changes in production efficiency. The time frame of analyses concerned 2006-2017, the spatial scope involved both the EU, the EU 15 (the so-called “old EU countries”), the EU 10 (“the new EU countries”) and individual EU countries. The subjective scope of the survey covered selected farms from the EU countries representing from 4 045 300 to 5 295 930 farms in the EU countries depending on the year. The data from the Farm Accountancy Data Network (FADN), a European system for accountancy data collection from agricultural holdings, were used. Total factor productivity (TFP) was evaluated using the Malmquist productivity index and non-parametric data envelopment analysis (DEA). The research found that over the period 2006-2017 the average level of positive changes of total factor productivity was similar in the old and new EU countries. At the same time, the increase in total productivity in the EU was mainly the result of an increase in efficiency, in the EU 15 it was the effect of positive changes in efficiency, while in the EU 10 it was due to both efficiency gains and technical progress. In 2006-2017, the greatest changes in technical progress were observed in the Czech Republic, and the highest increase in the efficiency of agricultural production in Ireland, while the decrease in the efficiency of agricultural production and technical regress of agriculture occurred only in Spain and Austria
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 114-126
Keywords: agriculture; total factor productivity; TFP; efficiency; technical progress; European Union; data envelopment analysis; rolnictwo; całkowita produktywność rolnictwa; efektywność; postęp techniczny; Unia Europejska